Urban public transport in Penang: Some policy considerations - Aziz, A.; Mohamad, J. (2013)
This paper illustrates the existing public transport policy framework at Federal, Regional, State, District and Council levels. It highlights specific policies which need to be taken into account at each level, as some remarkable improvements and integration are implemented on the public transport system in Penang. The useful information as found in this paper will subsequently be used to improve a policy-based assessment framework, which in turn serves to assess the performance of Penang public transport policy. This policy framework will attempt to repudiate the overarching need to come up with a final strategy, to assist in the delivery of policy objectives at all levels of the government. In order for the state’s urban public transport to be improved, it must have the support of the public, the politicians, and co-operation from all agencies including the Federal government itself.